Rekonstruksi Filsafat Ilmu Bagi Penguatan Pendidikan Kontemporer dalam Menjawab Tantangan dan Masa Depan Ilmu - Zainul Arasy; Efendi Efendi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The development of modern education requires a strong philosophical foundation to ensure that learning processes are not merely technical but oriented toward holistic human formation. This article aims to comprehensively analyze the role of the philosophy of science within contemporary education through a conceptual exploration grounded in an extensive literature review. The philosophy of science with its three major pillars: ontology, epistemology, and axiology serves as an analytical framework for understanding the nature of human beings, the structure of knowledge, and the values embedded within educational objectives. The research methodology employs the Miles and Huberman data analysis model, consisting of data reduction, data display, and conclusion drawing/verification. The findings indicate that the philosophy of science plays a strategic role in providing direction and orientation for the development of humanistic, adaptive, and globally responsive education. Moreover, this study reveals that the advancement of scientific knowledge encounters significant challenges, including ontological complexity, epistemological crises driven by digital disruption, moral degradation, and shifting scientific paradigms. In the age of artificial intelligence and globalization, the philosophy of science emerges as an ethical and methodological compass to ensure that scientific progress remains aligned with human welfare. This study underscores the urgency of reconstructing educational paradigms by integrating humanistic values, local wisdom, and modern scientific thought to realize a future of science that is ethical, sustainable, and dignified.